Transanal and transabdominal reinforcement of staple line of colorectal anastomosis as a method of prevention of its leakage: literature review - A. A. Balkarov; M. V. Alekseev; E. G. Rybakov; S. I. Sevostiyanov (Тазовая хирургия и онкология, 2019)
The decrease of frequency of postoperative complications and leakage of colorectal anastomosis is one of the most important and actual problem of colorectal surgery. The formation of preventive stoma is a standard method of colorectal anastomotic leakage prevention. However, this method can bear to postoperative complications and disable patients. In this review article we discuss the results of transabdominal and transanal reinforcement of colorectal anastomosis as a method of leakage prevention.